Existence of Phytoplankton in Waters Affected by Hot Water of Electric Steam Power Plant (ESPP) of Teluk Sirih as Ecological Bioindicator Reference for Climate Change Mitigation - Junialdi, Rezi; Merina, Gusna; Sari, Mistia; Mursyid, Ahmad; Alponsin, Alponsin; Drajat, Rian Rafiul; Sonia, Sonia (Program Pascasarjana Universitas Sriwijaya, 2024)
Electric Steam Power Plant (ESPP) in Teluk Sirih located on the seafront will certainly have an impact on changes in environmental factors such as physical, chemical and biological, one of which will be affected is phytoplankton. The research objective was to study the community structure of phytoplankton in the waters affected by the hot water of the ESPP of Teluk Sirih which was carried out in August 2023 with four sample stations namely Outfall, Inlet, Jetty and the middle of the sea as controls. The results of the study showed that the community structure of phytoplankton in the waters around the PLTU of Teluk Sirih was not significantly affected by hot water. This is illustrated by the diversity results which are classified as well H' ranging from 1.710-2.156. Evenest Index (E) 0.562-0.761 and Dominance Index (C) 0.188-0.295. The E and C values show that the phytoplankton are evenly distributed and no species dominates the ESPP of Teluk Sirih. The physics and chemistry of water are all above the quality standards of Ministry of Environment No. 51. 2004 as temperature ranges from 29-320C, pH 7-8, brightness >3m, Salinity 31,4-32,2 mg/L. Dissolved oxygen 5 mg/L, Carbon dioxide 48-62 mg/L, BOD5 4-5 mg/L, Nitrates 0.02-0.031 mg/L and orthophosphate 0.014-0.018.Keywords: Hot water, Phytoplankton, ESPP of Teluk Sirih, Community Structure and Physical Chemical Factors